One-Hop Neighbor Transmission Coverage Information Based Distributed Algorithm for Connected Dominating Set - Wenyong Wang; Jun Zhang; Yong Tang; Yu Xiang; Ting Yang (2010 3rd International Symposium on Parallel Architectures, Algorithms and Programming, 2010)
Broadcast is very important for delivering messages in wireless sensor networks. In order to improve the efficiency of broadcast and reduce energy consumption, it is necessary to construct a virtual backbone within the entire network. Constructing a virtual backbone is identical with calculating connected dominating set. 1-hop neighbor node transmission coverage information is used to calculate the minimum forwarding set distributively on each node of the network, and then the method of broadcasting information of minimal forwarding set is used to construct a connected dominating set. 1-hop neighbor transmission coverage information based distributed algorithm for connected dominating set is designed to get a small connected dominating set, while minimizing the cost of energy and time in the implementation of the algorithm. The simulation results show that the algorithm has achieved its purpose, fast convergence, low transmission traffic and reasonable connected dominating set.